2022
DOI: 10.3390/app12136781
|View full text |Cite
|
Sign up to set email alerts
|

Multirotor Unmanned Aerial Vehicle Configuration Optimization Approach for Development of Actuator Fault-Tolerant Structure

Abstract: Presently, multirotor unmanned aerial vehicles (UAV) are utilized in numerous applications. Their design governs the system’s controllability and operation performance by influencing the achievable forces and moments produced. However, unexpected causalities, such as actuator failure, adversely affect their controllability, which raises safety concerns about their service. On the other hand, their design flexibility allows further design optimization for various performance requirements, including actuator fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies, including our prior research, have demonstrated the ability to partially regain control authority in certain types of multirotor UAVs during mid-flight propulsion system failures [13][14][15]. Specifically, the hexarotor configuration noted in [16] exhibits enhanced resilience to actuator failures.…”
Section: Introductionmentioning
confidence: 91%
“…Numerous studies, including our prior research, have demonstrated the ability to partially regain control authority in certain types of multirotor UAVs during mid-flight propulsion system failures [13][14][15]. Specifically, the hexarotor configuration noted in [16] exhibits enhanced resilience to actuator failures.…”
Section: Introductionmentioning
confidence: 91%
“…The choice of the number and types of actuators, and how they are used in the vehicle design may improve its robustness wrt to faults. In [4], an optimization framework is presented to design a novel actuator fault-tolerant multrirotor MAV.…”
Section: Vehicle Design and Characterizationmentioning
confidence: 99%
“…In multirotor UAVs, the spinning propellers play a crucial role in generating forces and moments that impact the system dynamics. The configuration of a multirotor UAV is determined by parameters such as the position, orientation, and number of propulsion systems [24]. Throughout this article, the term "actuator" is used interchangeably to refer to the propulsion system, particularly the motor and propeller components.…”
Section: Review On Multirotor Uavs and Problem Definitionmentioning
confidence: 99%
“…Figure 3 illustrates the impact of the failed actuator's position on the attainable force and moment using the Attainable Moment Set (AMS) method. The AMS method is a powerful tool for understanding a system's control authority [24]. It imposes constraints on the maximum attainable time derivative of states, such as accelerations, which, in turn, limits maneuverability, trajectory agility, and disturbance rejection capabilities.…”
Section: Effect Of Actuator Failure On System Dynamicsmentioning
confidence: 99%